2019
DOI: 10.1055/s-0039-1694734
|View full text |Cite
|
Sign up to set email alerts
|

Neurotized Free Tissue Transfer for Foot Reconstruction: A Systematic Review

Abstract: Background Soft tissue reconstruction of the foot represents a complex reconstructive challenge given the unique anatomical properties of the glabrous plantar skin. For large soft tissue defects and/or complex injuries, free tissue transfer is often the optimal reconstructive modality. The decision to pursue a neurotized free flap remains controversial and an area of debate. Given the trend toward increasing use of neurotized free flaps, we performed a systematic review to determine if nerve coaptation is a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
(25 reference statements)
0
17
0
1
Order By: Relevance
“…Sensory recovery, among important functional outcomes, has consequently received increasing attention during flap selection (Graham & Dellon, 1995). However, the requirement of the nerve coaptation for sensate reconstruction during the free tissue transfer remains an area of debate (Rinkinen et al, 2020). It has been reported that crude sensation could be noted in noninnervated flaps (Rothenberger et al, 2019), possibly by means of nerve ingrowth from the recipient wound bed into the flaps (Graham & Dellon, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory recovery, among important functional outcomes, has consequently received increasing attention during flap selection (Graham & Dellon, 1995). However, the requirement of the nerve coaptation for sensate reconstruction during the free tissue transfer remains an area of debate (Rinkinen et al, 2020). It has been reported that crude sensation could be noted in noninnervated flaps (Rothenberger et al, 2019), possibly by means of nerve ingrowth from the recipient wound bed into the flaps (Graham & Dellon, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an innervated flap, in which a nerve coaptation is performed during the free tissue transfer (Kaplan, 1969), has been reported to provide functionally meaningful sensory recovery such as light touch, pain sensation, and 2PD. The return of sensory in innervated flaps is also earlier than that of noninnervated flaps (Rinkinen et al, 2020; Santanelli, Tenna, Pace, & Scuderi, 2002). Santanelli et al (2002) compared the outcomes of free forearm flaps with or without sensory nerve coaptation for sole reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidermal layer is significantly thicker with ∼1.4 mm when compared to the integument of other anatomical areas. [ 5 , 6 ] Moreover, numerous fibrous septae anchor the cutaneous tissue to the plantar aponeurosis, resulting in lower shearing forces during ambulation and lobules of subcutaneous adipose tissue serve as an optimal shock absorbent. [ 7 , 8 ] Finally, the plantar sensitivity allows precise pressure detection, which is essential for weight redistribution while standing.…”
Section: Introductionmentioning
confidence: 99%
“…Successful surgical repair and flap survival after transplantation are primary concerns, but reducing complications at the recipient site and achieving perfect reconstruction have long been the ultimate goal of reconstructive surgeons. Sensory disorders associated with ALT free‐flap reconstruction can result in poor functioning of repairs in regions such as the face, hands, feet, and perineum 5‐7 . Achieving a perfect repair with accelerated sensory recovery of recipient site has become a challenge to reconstructive surgeons.…”
Section: Introductionmentioning
confidence: 99%